2017
DOI: 10.1177/0969733017700238
|View full text |Cite
|
Sign up to set email alerts
|

How work setting and job experience affect professional nurses’ values

Abstract: The professional setting influenced the importance assigned to professional nursing values, and clear differences were observed between primary and hospital care. The domain of ethics was considered the most important. It is necessary to reflect on the significance attributed to professional values, especially in more expert nursing staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
20
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 18 publications
7
20
0
2
Order By: Relevance
“…The ethical values were considered to be the most important, followed by professional mastery and, lastly, professional commitment. These data are consistent with the results of a study on values, work setting and professional experience carried out with nurses in hospitals and primary care centres in Asturias, Spain (Fernández‐Feito et al ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The ethical values were considered to be the most important, followed by professional mastery and, lastly, professional commitment. These data are consistent with the results of a study on values, work setting and professional experience carried out with nurses in hospitals and primary care centres in Asturias, Spain (Fernández‐Feito et al ).…”
Section: Discussionsupporting
confidence: 91%
“…Generally, the importance attached to professional values was high, which is similar to findings in other studies carried out among nursing students (Alkaya et al ; Ayla et al ; Donmez & Ozsoy ) and professionals (Cetinkaya‐Uslusoy et al ; Fernández‐Feito et al ; Poorchangizi et al ). The ethical values were considered to be the most important, followed by professional mastery and, lastly, professional commitment.…”
Section: Discussionsupporting
confidence: 89%
“…The values on this dimension referred to the degree of social and professional involvement with the community, families, and patients that these students had not had the time or experience to rank accurately, unlike more experienced nurses [32]. Moreover, this reflects Spanish culture, which has little tradition of participation in professional associations [28]. This result correlates with the fact that values related to professional expertise are largely acquired and reinforced during postgraduate studies [3].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the EVPS has been culturally validated [18]. The EVPS scale has been used in Spanish speaking countries such as Colombia [19] and Spain [28,29].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies have revealed that employee's past work experience can produce their pro-social behaviour including pro-environmental behaviour [7] as well as affect their personal values [8]. Employee's past work experience increase the development of their professional values in their job which lead to be more quality and ethical.…”
Section: A Employee's Past Work Experiencementioning
confidence: 99%